On uniform convergence of wavelet expansions of some random processes - Perestyuk, M. (Інститут математики НАН України, 2006)
In the paper there are found conditions for uniform convergence with probability one of wavelet expansion of g-sub-Gaussian random processes under additional condition for norm of such process.